ESTIMATION OF BI-FUEL VEHICULAR EMISSION BY SYSTEM DYNAMICS APPROACH - M. Dwi Atmanto (Scientific Contributions Oil and Gas, 2003)
The growth in the number of vehicles in big cities is around 8-12% annually. In Indonesia the growth during the period of 1990 to 1998 was dominated by motor cycles (72%), passenger cars (15%), cargo cars (9%), buses (4%) the majority of which use oil fuel in the form of premix, gasoline or diesel oil.